Tindak Tutur Ekspresif dalam Komentar Youtube kanal Nihongo Mantappu episode “AKHIRNYA LULUS KULIAH! WISUDA WASEDA UNIVERSITY” - Ananda, Nadya Tri; Asnawi, Asnawi (Jurnal Bahasa dan Sastra, 2024)
A study on expressive speech acts in YouTube channel comments can provide valuable insights into various aspects of online interactions, such as community formation, negotiation of meaning, and expression of identity. The objective of this study is to describe the different forms and functions of expressive speech acts in the comments section of the YouTube video entitled "AKHIRNYA LULUS WISUDA! WISUDA WASEDA UNIVERSITY" on the Nihongo Mantappu channel. This video was posted in April 2022. The study employed a qualitative research design with a pragmatic approach to analyze the comments and identify the different expressive speech acts utilized by netizens. Three primary forms of expressive speech acts were identified in the comment section of Nihongo Mantappu's YouTube account: praising or expressing admiration, offering congratulations, and expressing gratitude towards others for their contributions. Overall, the study concluded that expressive speech acts play a significant role in online interactions and contribute to the formation of virtual communities.